Macro- and micro-morphological study of fruits and seeds in the genus Geranium (Geraniaceae) - Esfandani-Bozchaloyi, Somayeh; Sheidai, Masoud; Keshavarzi, Maryam (Phytotaxa, 2018)
Geranium (Geraniaceae) is a genus with 325 species worldwide. In present study fruit and seed morphology of 832 individuals from 23 taxa of Geranium were collected from different habitats in Iran. Samples were examined by use of light and scanning electron microscopy (SEM). The morphometric study involved 8 quantitative and 11 qualitative characters. Statistical analysis employed PAST software. Principal Component Analysis defined the most variable characters. Features as mericarp shape, mericarp and seed color, hair density, mericarp ornamentations and seed coat pattern were of diagnostic importance. Taxa of two subgenera are clearly separated based on selected fruit and seed characters. Seed macro and micro morphological characters were found useful for the taxonomic delimitations. Despite separation of the subgenera, some sections are mixed.